2013
DOI: 10.1371/journal.pone.0072968
|View full text |Cite
|
Sign up to set email alerts
|

Whole Transcriptome Analysis of Acinetobacter baumannii Assessed by RNA-Sequencing Reveals Different mRNA Expression Profiles in Biofilm Compared to Planktonic Cells

Abstract: Acinetobacter baumannii has emerged as a dangerous opportunistic pathogen, with many strains able to form biofilms and thus cause persistent infections. The aim of the present study was to use high-throughput sequencing techniques to establish complete transcriptome profiles of planktonic (free-living) and sessile (biofilm) forms of A . baumannii ATCC 17978 and thereby identify differences in their gene expression patterns. Collections of mRNA from planktonic (both exponential and stationary phase cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
141
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(151 citation statements)
references
References 71 publications
9
141
0
1
Order By: Relevance
“…It is the case of AdeI (A1S_2735) and AdeJ (A1S_2736) that belong to the constitutive AdeIJK efflux pump, as well as an inner membrane protein (A1S_3446) and a membrane fusion protein (A1S_3447) that are, to our knowledge, described for the first time. These two last efflux pumps are part of a RND efflux system and are different from those found as up-regulated in S-L biofilms (25,27) and so highlight the specificity of A-L biofilms. The AdeIJK efflux pump has a high broad substrate specificity; its overexpression in A. baumannii would confer a low bacterium susceptibility to major antibiotic classes, including ␤-lactams, fluoroquinolones, tetracyclines, phenicols, antifolates, and fusidic acid (45).…”
Section: Increase Of Drug Resistance and Stress Adaptation Proteins Bmentioning
confidence: 75%
See 1 more Smart Citation
“…It is the case of AdeI (A1S_2735) and AdeJ (A1S_2736) that belong to the constitutive AdeIJK efflux pump, as well as an inner membrane protein (A1S_3446) and a membrane fusion protein (A1S_3447) that are, to our knowledge, described for the first time. These two last efflux pumps are part of a RND efflux system and are different from those found as up-regulated in S-L biofilms (25,27) and so highlight the specificity of A-L biofilms. The AdeIJK efflux pump has a high broad substrate specificity; its overexpression in A. baumannii would confer a low bacterium susceptibility to major antibiotic classes, including ␤-lactams, fluoroquinolones, tetracyclines, phenicols, antifolates, and fusidic acid (45).…”
Section: Increase Of Drug Resistance and Stress Adaptation Proteins Bmentioning
confidence: 75%
“…Today, transcriptomic (25) and proteomic (26,27) studies are performed to investigate the physiology of S-L A. baumannii biofilms. Only a proteomic work focused on the membrane compartment of pellicle bacteria (28) and to our knowledge, no comparative study was performed to give information on the protein expression dynamics during the pellicle formation.…”
mentioning
confidence: 99%
“…Of note is the removal of the genes mrkC (pilin) and mrkD (assembly chaperone), which are part of chaperone-usher (CU) system assembling pili. It was previously shown that the disruption of such pili CU systems, like Csu or Fim, induce a severe decrease in biofilm formation in A. baumannii (17,18). The loss of these genes and of the genomic element was confirmed by Sanger sequencing and by whole-genome mapping (data not shown) (19).…”
mentioning
confidence: 66%
“…The increasing availability of bacterial genome sequences and genomewide association tools, such as transcriptome and comparative genome analysis, have led to the identification of various genes that play important roles in the pathogenesis of A. baumannii (5)(6)(7). This circumstance has given rise to the need for fast and efficient gene disruption systems, which are critical tools for the functional analysis of genes.…”
mentioning
confidence: 99%